A política de inovação e a formação do químico - Sérgio de Paula Machado (Química Nova, 2013)
In December 2004, Brazil's President signed Law number 10.973, which provides for incentives toward innovation, scientific and technological research in the production environment and other measures, also known as the Law of Innovation. Although Brazil has advanced greatly in the number of scientific articles published, currently accounting for about 3% of world scientific output, this progress has not been replicated in the production of patents. This article presents a discussion on the importance of introducing patent issues into national undergraduate courses.